Patterns of use and satisfaction with a university-based teleradiology system...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: performance improvement in radiology.' Houston TX, May 6-9, 1999 - Krupinski EA; McNeill K; Ovitt TW; Alden S; Holcomb M (Journal of Digital Imaging)
The Radiology Department at the University of Arizona has been operating a teleradiology program for almost 2 years. The goal of this project was to characterize the types of cases reviewed, to assess radiologists' satisfaction with the program, and to examine case turnaround times. On average, about 50 teleradiology cases are interpreted each month. Computed tomography (CT) cases are the most common type of case, constituting 65% of the total case volume. Average turnaround time (to generate a 'wet read' once a case is received) is about 1.3 hours. Image quality was rated as generally good to excellent, and the user interface as generally good. Radiologists' confidence in their diagnostic decisions is about the same as reading films in the clinical environment. The most common reason for not being able to read teleradiology images is poor image quality, followed by lack of clinical history and not enough images. Copyright (c) 1999 by W.B. Saunders Company